Identification of compositional and structural changes in the nucleus pulposus of patients with cervical disc herniation by Raman spectroscopy - Wang, Zhiqi; Xue, Tao; Zhang, Tongxing; Wang, Xuehui; Zhang, Hui; Gao, Zhongyu; Zhou, Qiang; Gao, Erke; Zhang, Tao; Li, Zhaoyang (Frontiers in Endocrinology, 2022)
Purpose: Cervical disc herniation (CDH) is one of the most common spinal diseases in modern society, the intervertebral disc degeneration (IVDD) has long been considered as its primary cause. However, the mechanism of intervertebral disc degeneration is still unclearly state. The aim of the study is to examine the components and structures of proteoglycan and collagen in cervical disc herniated nucleus pulposus (NP) using a validated conveniently Raman spectra technique to further elucidate the mechanism of IVDD at the microscopic level. Methods: Our study used a burgeoning technique of Raman spectroscopy that combined with vitro intervertebral disc NP to characterize the above research purposes. Firstly, we collected cervical disc NP samples and imaging data by certain inclusion and exclusion criteria. Then, we graded the NP of the responsible segment according to the patient's preoperative cervical Magnetic Resonance Imaging (MRI) T2-weighed images by Pfirrmann grading criteria meanwhile measuring the T2 signal intensity value of NP. Finally, the samples were scanned and analyzed by Raman spectroscopy. Results: A total of 28 nucleus pulposus tissues from 26 patients (Two of these patients involved two segments) with cervical disc herniation were included in this study. According to the Raman spectroscopy scanned, the relative content of proteoglycans which characterized by the ratio of the two peaks (I1064/I1004) in the NP showed a significantly negative correlation with Pfirrmann grade (P<0.001),while the collagen content and the NP intensity value showed a positive correlation(P<0.001).For the microstructural characterization of collagen, we found that it may have an essential role in the degenerative process of intervertebral disc. Conclusion: The present study demonstrated the possibility of characterizing the macromolecular substances inside the cervical disc nucleus pulposus tissue by Raman spectroscopy. It also confirmed that macromolecular substances such as proteoglycans and collagen have some degree of alteration in content and structure during degeneration, which has further positive significance for the elucidation of CDH's mechanism.